Editorial: Special issue on the work of Vilhjálmur Árnason - Kadri Simm; Bjørn Hofmann (Etikk i Praksis: Nordic Journal of Applied Ethics)
The editorial introduces the rationale for putting together the special issue on the works of Vilhjalmur Arnason, discusses some of the main themes of his corpus and gives and overview of the published commentaries.